Body weight changes and incidence of cachexia after stroke. Issue 3 (24th January 2019) - Scherbakov, Nadja; Pietrock, Charlotte; Sandek, Anja; Ebner, Nicole; Valentova, Miroslava; Springer, Jochen; Schefold, Joerg C.; von Haehling, Stephan; Anker, Stefan D.; Norman, Kristina; Haeusler, Karl Georg; Doehner, Wolfram
Abstract: Background: Body weight loss is a frequent complication after stroke, and its adverse effect on clinical outcome has been shown in several clinical trials. The purpose of this prospective longitudinal single‐centre observational study was to investigate dynamical changes of body composition and body weight after ischemic stroke and an association with functional outcome. Methods: Sixty‐seven consecutive patients (age 69 ± 11 years, body mass index 27.0 ± 4.1 kg/m 2, 42% female patient, mean ± SD) with acute ischemic stroke with mild to moderate neurological deficit (National Institute of Health Stroke Scale median 4, ranged 0–12) were analysed in the acute phase (4 ± 2 days) and at 12 months (389 ± 26 days) follow‐up. Body composition was examined by dual energy X‐ray absorptiometry. Cachexia was defined according to the consensus definition by body weight loss ≥5% within 1 year and additional clinical signs. Lean tissue wasting was considered if a ratio of upper and lower limbs lean mass sum to squared height (kg/m 2 ) was ≤5.45 kg/m 2 for female patient and ≤7.25 kg/m 2 for male patient. Results: According to the body weight changes after 12 months, 42 (63%) patients had weight gain or stable weight, 11 (16%) patients had moderate weight loss, and 14 (21%) patients became cachectic. A relative decline of 19% of fat tissue and 6.5% of lean tissue was observed in cachectic patients, while no changes of lean tissue were observed in non‐cachectic patients after 12 months. The modified Rankin Scale was 48% higher (2.1 ± 1.6, P  < 0.05), Barthel Index was 22% lower (71 ± 39, P  < 0.01), and handgrip strength was 34% lower (21.9 ± 13.0, P  < 0.05) in cachectic compared to non‐cachectic patients after 12 months. The low physical performance if defined by Barthel Index <60 points was linked to the lean tissue wasting (OR 44.8, P  < 0.01), presence of cachexia (OR 20.8, P  < 0.01), and low body mass index <25 kg/m 2 (OR 11.5, P  < 0.05). After adjustment for cofounders, lean tissue wasting remained independently associated with the low physical performance at 12 months follow‐up (OR 137.9, P  < 0.05). Conclusions: In this cohort study, every fifth patient with ischemic stroke fulfilled the criteria of cachexia within 12 months after index event. The incidence of cachexia was 21%. Cachectic patients showed the lowest functional and physical capacity.